Efektifitas PBL terhadap Kemampuan Pemecahan Masalah pada Kelas V Tema 5 Ekosistem Subtema 2 Hubungan Antar Makhluk Hidup dalam Ekosistem di SD Supriyadi - Devi Ariyanti Lestari; Husni Wakhyudin; Farida Nursyahidah; Aini Istikomah (Journal on Education, 2023)
Educators play an important role in the teaching and learning process in schools. Students will easily understand learning material if it is delivered in an effective way. Currently, the world of education requires student-centered learning by using a learning model, one of which is problem-based learning, therefore researchers are interested in raising research with the title "Effectiveness of PBL on Problem Solving Ability in Class V theme 5 Ecosystem, sub-theme 2 Relationships between Living Things in the Ecosystem at SD Supriyadi Semarang". The purpose of this study is to determine the effectiveness of the problem-based learning model for class Vb students at SD Supriyadi Semarang. The type of research used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The researcher made observations regarding the basic understanding of the students first and saw the characters in class Vb SD Supriyadi Semarang. The interview was conducted in an indirect way, namely by distributing questionnaires in the form of questions regarding students' responses. And documentation in the form of collecting student products, taking photos and videos. Furthermore, the data is reduced to compile this article. The research subjects were researchers and students of class Vb SD Supriyadi Semarang. The results of the research show that the problem-based learning model has good effectiveness with 2D product assessment, as well as a questionnaire to find out students' responses in optimizing students' understanding of the subject matter. Students have the freedom to think, discuss, express opinions, so that they find solutions to existing problems.